2016
DOI: 10.1016/j.dadm.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vascular risk factors, statins, and antihypertensive drugs on PiB deposition in cognitively normal subjects

Abstract: IntroductionHypertension, hypercholesterolemia, and obesity increase the risk of dementia. Although their detection is commonly followed by an introduction of treatment, little is known about how medications frequently used to treat vascular risk affect amyloid deposition.MethodsA cross-sectional study of 156 subjects who underwent positron emission tomography with PiB. Using linear regression, we tested whether blood pressure, cholesterol, overweight/obese status, angiotensin receptor blockers (ARBs), beta-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
4
21
0
Order By: Relevance
“…The present study assesses a large pathologic series of FTD syndromes without AD and reports Ab deposition in 38% (21/56) in patients with bvFTD, 37% (14/38) in patients with PPA, and 57% (8/14) in age-matched controls. The presence and topographical progression of Ab increased with age in FTD, as observed in controls [23,24]. In particular, our results are consistent with recent results showing that the transition to amyloidosis in the population without substantive neurodegeneration is greatest between 60 and 75 years of age [25].…”
Section: Discussionsupporting
confidence: 92%
“…The present study assesses a large pathologic series of FTD syndromes without AD and reports Ab deposition in 38% (21/56) in patients with bvFTD, 37% (14/38) in patients with PPA, and 57% (8/14) in age-matched controls. The presence and topographical progression of Ab increased with age in FTD, as observed in controls [23,24]. In particular, our results are consistent with recent results showing that the transition to amyloidosis in the population without substantive neurodegeneration is greatest between 60 and 75 years of age [25].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, a recent statement by the World Dementia Council suggested that "Regular physical activity and management of cardiovascular risk factors (e.g., diabetes, obesity, smoking, and hypertension) are associated with a reduced risk of cognitive decline and may reduce the risk of dementia" [288,289]. A recent cross-sectional study concluded that the use of certain medications to treat vascular disease, especially angiotensin receptor blockers and diuretics, may decrease Ab accumulation [290]. In a recent review, Deckers et al (2015) [291] found that the most common modifiable risk factors for AD development included hypertension, diabetes, midlife obesity, physical inactivity, hyperlipidemia, and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature suggests that the vascular risk factors comprising MetS are associated with Aβ accumulation. Specifically, amyloid deposition has been associated with obesity [12], diabetes [13], cholesterol levels [14, 15], and hypertension [16, 17]. Though multiple review articles highlight the disruption in Aβ metabolism as a potential link between the development of MetS and AD [18, 19], the neuropathological association between MetS and cerebral Aβ has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%